Perubahan Aktivitas Ekonomi dan Pemanfaatan Lahan di Koridor Jalan Pantura Setelah Beroperasi Jalan Tol Cipali - Khairunisa Safira; Willy Arafah; Sugihartoyo Sugihartoyo; Marselinus Nirwan Luru (Jurnal Lingkungan dan Kota, 2021)
The existence of Pantura road as a physical facility is to support the daily needs of the people surrounding the Pantura Eretan Kulon Road. However, the operation of the Cikopo-Palimanan (Cipali) toll road in June 2015 caused the movement switch from Pantura Road to the Cipali toll road given a change in economic activity and land use in Pantura Eretan Road Corridor. The purposes of this study are to identify changes in economic activities and land use after the operation of the Cipali toll road by comparing the economic activities and land changes in the year of 2014 and 2019. Spatial analysis method and descriptive statistical analysis method were used in this study. The results of the analysis show that the operation of the Cipali toll road have led to a decrease in the number of business activities, especially the food business, a decreased income in the Pantura Road Corridor which is still below the Regency Minimum Wage (UMK) Indramayu and based on BPS is still low, changes conversion of the widest land use function in trade and services to become yard land which has no economic value, and a decrease in land use based on the function of buildings in the corridor of Jalan Pantura which is dominated by restaurants. On the other hand, the operation of the Cipali toll road results in a decrease of traffic volume on Jalan Pantura due to the reduced traffic generation so that the traffic congestion is reduced.